1991
DOI: 10.1056/nejm199106063242301
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Accessory Atrioventricular Pathways (Wolff–Parkinson–White Syndrome) by Radiofrequency Current

Abstract: Radiofrequency current is highly effective in ablating accessory pathways, with low morbidity and no mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
381
3
16

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,332 publications
(409 citation statements)
references
References 33 publications
9
381
3
16
Order By: Relevance
“…Most AF in patients with Wolff-Parkinson-White syndrome is transient while electrical cardioversion or antiarrhythmic drugs is necessary in some patients. In these patients, the first line of therapy is radiofrequency catheter ablation (RFCA) during sinus rhythm (3,4). Here, we report a rare case of Wolff-Parkinson-White syndrome with persistent/-permanent AF, whose ventricular response via an accessory pathway was progressively facilitated.…”
Section: Introductionmentioning
confidence: 99%
“…Most AF in patients with Wolff-Parkinson-White syndrome is transient while electrical cardioversion or antiarrhythmic drugs is necessary in some patients. In these patients, the first line of therapy is radiofrequency catheter ablation (RFCA) during sinus rhythm (3,4). Here, we report a rare case of Wolff-Parkinson-White syndrome with persistent/-permanent AF, whose ventricular response via an accessory pathway was progressively facilitated.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In addition, previous studies have shown a greater complication rate for RFCA in children weighing Ͻ15 kg. 4,10 Although limited intermediate-term follow-up studies have revealed no significant increase in ventricular arrhythmias 11,12 and no evidence of coronary abnormalities by traditional angiography at up to 6 months after ablation, 12 a report of late development of asymptomatic coronary artery stenosis after right free wall RFCA in 2 young boys with Ebstein's malformation 13 and a report from the Pediatric Ablation Registry of a very small number of procedure-related late deaths after the ablation procedure suggest some caution in the use of RFCA in the younger pediatric population in general. 14 As yet, no data have been published to assess the long-term risks of RF lesions on myocardial function, coro-nary perfusion, or arrhythmogenicity in a group of developing infants and children.…”
mentioning
confidence: 99%
“…Catheter ablation of the accessory pathway with radiofrequency energy has been performed with a high success rate and low incidence of complications [3] [4]. In radiofrequency catheter ablation, radiofrequency energy is delivered from an external generator and destroys tissue by controlled heat production [5] and complications such as atrioventricular block, right atrial thrombus, pericarditis, coronary spasm, cardiac tamponade have been reported in the literature [6] [7]. Hindricks reported that in patients with left-sided atrioventricular AP, placement of electrode catheter into the coronary sinus may damage the small branch of the coronary vein and may result in cardiac tamponade [8].…”
Section: Commentmentioning
confidence: 99%